РОЛЬ СТОРОЖЕВЫХ ЛИМФАТИЧЕСКИХ УЗЛОВ В СТАДИРОВАНИИ РАКА ЖЕЛУДКА. - Юсупов А.П.,; Тулкинов Х.Х,; Абдуллаев О.Б, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Alfraganus University г. Ташкент, Узбекистан.  Abstract: Stomach cancer remains one of the leading causes of cancer mortality worldwide.  Radical  gastrectomy  with  D2  volume  lymphodissection  is  the  "gold standard" of surgical treatment, however, it is associated with a significant frequency of postoperative complications. In recent decades, the concept of sentinel lymph node biopsy (BSLU) has been actively developing as an alternative, less invasive method for staging lymphogenic metastasis. Having initially proven its effectiveness in breast cancer and melanoma, this approach is also being adapted for stomach cancer. This review  analyzes  modern  methods  for  identifying  sentinel  nodes,  their  diagnostic accuracy,  clinical  advantages  and  disadvantages,  and  discusses  the  prospects  for introducing BSL into routine practice for the personalized treatment of patients with early  forms  of  stomach  cancer.  Special  attention  is  paid  to  combined  detection methods,  including  the  radioisotope  method  and  fluorescent  navigation  with indocyanine  green  (ICG),  which  demonstrate  the  highest  accuracy.  Despite  the promising  results,  the  heterogeneity  of  the  data  and  the  risk  of  false  negative conclusions still limit the widespread use of the technique outside of clinical trials.